Long Noncoding RNA MALAT1 Promotes Aggressive Pancreatic Cancer Proliferation and Metastasis via the Stimulation of Autophagy - Li, Le; Chen, Hua; Gao, Yue; Wang, Yong-Wei; Zhang, Guang-Quan; Pan, Shang-Ha; Ji, Liang; Kong, Rui; Wang, Gang; Jia, Yue-Hui; Bai, Xue-Wei; Sun, Bei (Molecular cancer therapeutics, 2016)
Recently, pancreatic ductal adenocarcinoma (PDAC) has emerged as one of the most aggressive malignant tumors with the worst prognosis. Previous studies have demonstrated that long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is increased in pancreatic cancer and is identified as a diagnostic biomarker. Nonetheless, the molecular mechanism of elevated MALAT1 levels and tumor aggressiveness remains unknown. In this study, MALAT1 was found to be highly expressed in PDAC tissues, and elevated expression was associated with poorer prognoses. In addition, MALAT1 was positively linearly correlated with the expression of LC3B mRNA. Furthermore, several molecules involved in cellular autophagic flux were modulated following the downregulation of MALAT1, including LC3, P62, and LAMP-2. Mechanistically, we found that MALAT1 interacted with RNA binding protein HuR, and silencing of MALAT1 greatly enhanced the posttranscriptional regulation of TIA-1 and had further effects on inhibiting autophagy. MALAT1 was speculated to regulate tumorigenesis via HuR-TIA-1–mediated autophagic activation. Hence, we investigated the biological properties of MALAT1 in terms of tumor proliferation and metastasis by promoting autophagy in vitro. In brief, these data demonstrate that MALAT1 could facilitate the advanced progression of tumors in vivo. Our study highlights the new roles of MALAT1 on protumorigenic functioning and anticancer therapy via activating autophagy in pancreatic cancer. Mol Cancer Ther; 15(9); 2232–43. ©2016 AACR.